PENGARUH PENDIDIKAN KESEHATAN MELALUI MEDIA LEAFLET DAN WHATSAPP TERHADAP PENINGKATAN PENGETAHUAN IBU MENYUSUI - Yuni ansi Ermitha; Yuniarti Yuniarti (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
Abstract Coverage of exclusive breastfeeding for babies in Central Kalimantan Province in 2017 reached 11.1% lower than the national target of breastfeeding at 80%. One of the reasons for not providing exclusive breastfeeding is because of the low knowledge of mothers and families about the benefits of breastfeeding. Health education has been carried out with various media such as leaflets but is still unclear and less attractive. Whatsapp media is expected to be more interesting and easy to understand. The general objective is to analyze the effect of health education through leaflet and whatsapp media on increasing the knowledge of breastfeeding mothers in the Bukit Hindu Community Health Center in Palangka Raya. This type of research is a quasi experiment with the Control Group Pretest-Postest Design approach. The analysis was carried out with the Mann Whitney test and the Wilcoxon Signed Rank Test. The results showed there was a significant effect on increasing knowledge before and after being given treatment to the leaflet group (p = 0.002). there is a significant effect on increasing knowledge before and after being given treatment to the whatsapp group (p = 0,000). Keywords: Health Education, Knowledge, Nursing Mothers